REPRESENTASI SIFAT MANUSIA DALAM KARAKTER ANIMASI STUDI ANALISIS SEMIOTIKA DALAM FILM ANIMASI “THE ANGRY BIRDS” - Muhamad Hasan Basori (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
This study aims to determine how the representation of human nature is depicted in Angry Birds The Movie. The method uses a qualitative approach with descriptive analysis. The focus of this research is visual analysis, namely on shapes, colors and gestures. Data analysis used Roland S. Barthes' semiotics to see two levels of meaning, denotative meaning and connotative meaning. The results showed that there is a form of denotation and connotation meaning, representing human nature in each of the main characters in The Angry Birds Movie, starting from Red depicted in red, Chuck in yellow, Bomb in black, Matilda in white and Terence in red. old, these characters have a concept of good visual communication in character creation, both in terms of physical appearance, color, and character.